Thomas Riis: Should Auld Acquaintance Be Forgot ... . Scottish-Danish Relations c. 1450-1707. Vol. HI. (Odense University Press, 1988). 296 + 393 s., ill. - J. V. Jespersen, Knud (Historie/Jyske Samlinger, 1991)
-